Synthesis of Chalcones and Flavanones in The Absence of Metal Ion - JAGANNADHA REDDY, N.; NARENDRA KUMAR, M.; MURALI, M.; SATYANARAYANA, P.V.V. (Asian Journal of Chemistry, 2010)
2'-Hydroxychalcones were synthesized in alkaline medium after trapping the metal ion of the hydroxide and sodium ethoxide with the crown ether. Synthesis of chalcone with bases like tetramethyl-ammonium hydroxide, and tetra-n-butyl ammonium hydroxide met with failure. But, flavanones were formed from the corresponding 2'-hydroxychalcone using alkaline medium without the metal ion, using tetramethyl ammonium hydroxide and tetra-n-butyl ammonium hydroxide.